2020
DOI: 10.11622/smedj.2019143
|View full text |Cite
|
Sign up to set email alerts
|

SAMe-TT2R2 score for prediction of suboptimal time in therapeutic range in a Thai population with atrial fibrillation

Abstract: Online first papers have undergone full scientific review and copyediting, but have not been typeset or proofread. To cite this article, use the DOIs number provided. Mandatory typesetting and proofreading will commence with regular print and online publication of the online first papers of the SMJ.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…[19] Rungroj et al studied 1669 patients including 22 centers across Thailand and found that the SAMe-TT 2 R 2 score was the only independent predictor of sub-optimal TTR among NVAF patients treated with warfarin. [20] However, there are some studies that shows this score cannot do so. A systematic review and simulation meta analysis conducted by Miert et al pointed out that although the SAMe-TT 2 R 2 score could predict low TTR, it's effect was limited and not very useful clinically [21] .…”
Section: Discussionmentioning
confidence: 99%
“…[19] Rungroj et al studied 1669 patients including 22 centers across Thailand and found that the SAMe-TT 2 R 2 score was the only independent predictor of sub-optimal TTR among NVAF patients treated with warfarin. [20] However, there are some studies that shows this score cannot do so. A systematic review and simulation meta analysis conducted by Miert et al pointed out that although the SAMe-TT 2 R 2 score could predict low TTR, it's effect was limited and not very useful clinically [21] .…”
Section: Discussionmentioning
confidence: 99%
“…Sus principales desventajas incluyen las marcadas interacciones farmacológicas y dietéticas, y el requisito de una monitorización de la coagulación seriada mediante el estudio del INR. Es así que se ha descrito en distintas series de casos un porcentaje cercano a 40-60% de pacientes que presentan una ACO subóptima con warfarina, definida como un tiempo en rango terapéutico < 65% (53,54) . El score SAMe-TT2R2 incluye como variables el sexo, la edad, los antecedentes patológicos, los fármacos concomitantes, el tabaquismo y la raza, y ha demostrado ser un buen predictor de una ACO subóptima con el uso de warfarina (52,54) , con valores > 3 puntos es preferible utilizar ACOD (19) .…”
Section: A) ¿Qué Riesgo Hemorrágico Y Trombótico Presenta El Paciente?unclassified
“…Poor time in therapeutic range (TTR) is another problem that is common among AF patients taking warfarin. Use of the SAMe-TT 2 R 2 score was recently proposed to predict poor TTR [ 15 22 ]. Recent European guidelines recommend considering VKA or NOACs if a patient’s SAMe-TT 2 R 2 score is within the range of 0–2 [ 1 ].…”
Section: Introductionmentioning
confidence: 99%